Cortical Auditory Evoked Potentials Reveal Changes in Audibility with Nonlinear Frequency Compression in Hearing Aids for Children: Clinical Implications - Ching, Teresa Y. C. (Semin Hear, 2016)
Hearing loss in children is detected soon after birth via newborn hearing screening. Procedures for early hearing assessment and hearing aid fitting are well established, but methods for evaluating the effectiveness of amplification for young children are limited. One promising approach to validating hearing aid fittings is to measure cortical auditory evoked potentials (CAEPs). This article provides first a brief overview of reports on the use of CAEPs for evaluation of hearing aids. Second, a study that measured CAEPs to evaluate nonlinear frequency compression (NLFC) in hearing aids for 27 children (between 6.1 and 16.8 years old) who have mild to severe hearing loss is reported. There was no significant difference in aided sensation level or the detection of CAEPs for /g/ between NLFC on and off conditions. The activation of NLFC was associated with a significant increase in aided sensation levels for /t/ and /s/. It also was associated with an increase in detection of CAEPs for /t/ and /s/. The findings support the use of CAEPs for checking audibility provided by hearing aids. Based on the current data, a clinical protocol for using CAEPs to validate audibility with amplification is presented.